Detection of Dobrava hantavirus RNA in Apodemus mice in Bulgaria. Issue 2 (4th August 2014) - Christova, Iva; Plyusnina, Angelina; Gladnishka, Teodora; Kalvatchev, Nikolay; Trifonova, Iva; Dimitrov, Hristo; Mitkovska, Vesela; Mohareb, Emad; Plyusnin, Alexander
<x xml:space="preserve">Abstract</x> Several Hantaviruses cause hemorrhagic fever with renal syndrome (HFRS) in Europe: Dobrava‐Belgrade virus (DOBV), Puumala, Saaremaa, Sochi, and Seoul virus. Although HFRS is endemic in Bulgaria, genome sequences of hantaviruses have never been detected in wild rodents. To identify rodent reservoirs, a total of 691 rodents from three endemic regions were trapped in 2011–2012 and screened by TaqMan RT‐PCR for detection of hantaviral genomic RNA. Partial small (S) and/or large (L)‐segment sequences were recovered from six Apodemus mice: five of the species A. flavicollis and one A. agrarius. Phylogenetic analysis revealed that all recovered sequences belonged to DOBV. On the phylogenetic trees, the novel Bulgarian hantavirus sequences clustered together with sequences of established previously DOBV variants recovered from Bulgarian HFRS patients and also with variants found in wild rodents trapped in Slovenia, Greece, and Slovakia. One of the novel Bulgarian DOBV S‐sequences from A. agrarius was related closely to DOBV sequences recovered from A. flavicollis, suggesting a spillover of DOBV from its natural host to A. agrarius mice. The results of this study confirmed the circulation of DOBV in wild rodents in Bulgaria. The complexity of the epidemiological situation in the Balkans requires further studies of hantaviruses in rodent hosts and human HFRS cases. J. Med. Virol. 87:263–268, 2015. © 2014 Wiley Periodicals, Inc.